Strain Identity of the Ectomycorrhizal Fungus Laccaria bicolor Is More Important than Richness in Regulating Plant and Fungal Performance under Nutrient Rich Conditions - Hazard, Christina; Kruitbos, Laura; Davidson, Hazel; Mbow, Fatou T.; Taylor, Andy F. S.; Johnson, David (Frontiers in Microbiology, 2017)
Effects of biodiversity on productivity are more likely to be expressed when there is greater potential for niche complementarity. In soil, chemically complex pools of nutrient resources should provide more opportunities for niche complementarity than chemically simple pools. Ectomycorrhizal (ECM) fungal genotypes can exhibit substantial variation in nutrient acquisition traits and are key components of soil biodiversity. Here, we tested the hypothesis that increasing the chemical complexity and forms of soil nutrients would enhance the effects of intraspecific ECM diversity on host plant and fungal productivity. In pure culture, we found substantial variation in growth of strains of the ECM fungus Laccaria bicolor on a range of inorganic and organic forms of nutrients. Subsequent experiments examined the effects of intraspecific identity and richness using Scots pine (Pinus sylvestris) seedlings colonized with different strains of L. bicolor growing on substrates supplemented with either inorganic or organic forms of nitrogen and phosphorus. Intraspecific identity effects on plant productivity were only found under the inorganic nutrient amendment, whereas intraspecific identity affected fungal productivity to a similar extent under both nutrient treatments. Overall, there were no significant effects of intraspecific richness on plant and fungal productivity. Our findings suggest soil nutrient composition does not interact strongly with ECM intraspecific richness, at least under experimental conditions where mineral nutrients were not limiting. Under these conditions, intraspecific identity of ECM fungi becomes more important than richness in modulating plant and fungal performance.